2014
DOI: 10.1267/ahc.14013
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Phagocytosis of Platelets in the Early Phase of 2,4,6-trinitro-1-chlorobenzene (TNCB)-induced Dermatitis in Mice

Abstract: Activated platelets form platelet–leukocyte aggregates in the circulation in inflammatory diseases. We investigated whether activated platelets in inflamed skin tissues are phagocytized and removed by neutrophils. To investigate the kinetics of platelets and neutrophils, we immunohistochemically examined the spatiotemporal distribution of them in a murine model of 2,4,6-trinitro-1-chlorobenzene (TNCB)-induced dermatitis by using confocal and structured illumination microscopy. Four hours after elicitation, agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Interestingly, investigation of the interaction among platelets, neutrophils, and endothelial cells in the CHS has shown that aggregates of platelets and neutrophils adhere to endothelial cells within vessels at 4 h after allergen challenge (Fig. 4) [40]. In addition, at 4-8 h after elicitation, platelets begin to be phagocytized by neutrophils, and neutrophils ingesting fragmented platelets are found inside vessels.…”
Section: Allergic Contact Dermatitismentioning
confidence: 95%
“…Interestingly, investigation of the interaction among platelets, neutrophils, and endothelial cells in the CHS has shown that aggregates of platelets and neutrophils adhere to endothelial cells within vessels at 4 h after allergen challenge (Fig. 4) [40]. In addition, at 4-8 h after elicitation, platelets begin to be phagocytized by neutrophils, and neutrophils ingesting fragmented platelets are found inside vessels.…”
Section: Allergic Contact Dermatitismentioning
confidence: 95%
“…In contact dermatitis, recurring exposure to various chemicals elicit activated platelets, which shed microparticles, secrete growth factors, coagulation factors, and chemokines, induces leukocyte recruitment into the skin by forming platelet–leukocyte aggregates. These platelet‐leukocyte aggregates in circulation are known to play a major role in the early phase of skin inflammation …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to detecting the ER dimers, we could distinctively identify the complex patterns of ER dimer with cofactor proteins using N-SIM. Furthermore, N-SIM analysis also could indeed evaluate fine structures and function in single living cell [ 5 , 12 , 31 ]. This could allow evaluation of dynamic changes in ERα and ERβ dimer formation using N-SIM analysis.…”
Section: Discussionmentioning
confidence: 99%